Pengaruh Merger dan Religiusitas Terhadap Perilaku Berpindah (Switching Behaviour) Nasabah BSI - Cahyani, Maya Septi; Budiyah, Feriani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
This study aims to analyze the effect of mergers and religiosity on switching behaviour of customers BSI users who live in DKI Jakarta Province. This study is quantitative research using Multiple Linear Regression via Microsoft Excel 2010 and SPSS version 26. The population of this research, customers BSI users, was sampled as many as 100 respondents using the Purposive Sampling technique. Data was collected using a questionnaire on google form. The research results show that mergers and religiosity simultaneously have a significant effect on Switching Behaviour. Partially, the merger has a positive and significant effect on Switching Behaviour, so that you have a good opportunity to move now or in the future. Likewise, religiosity has a positive and significant effect on switching behaviour. It is important for management to pay attention to customer switching behavior, because this will affect the target number of customer increases that the bank wants to achieve. Keywords : Effect of Merger, Influence of Religiosity, Switching Behaviour, Indonesian Bank Syariah (BSI) Customers